Understanding a pedagogy of teacher education contexts for teaching and learning about your educational practice - Butler, Brandon M.; Bullock, Shawn Michael 1976- (Routledge, 2024)
"Providing readers with insights and examples of how teacher educators learn and teach a pedagogy of teacher education (PTE), Butler and Bullock organize a wholistic and practical resource for the next generation of teacher educators. Expanding on the highly referenced scholarship of John Loughran and Tom Russell, "Understanding a Pedagogy of Teacher Education" explores the learning of PTE through individual and collaborative endeavors, and large-scale institutional and cross-national initiatives. Contributors highlight their experiences teaching PTE in formal learning spaces, in international workshop settings, and on the program-wide scale in order to uncover how they came to understand PTE and enact it effectively. Each chapter connects broad strokes concepts of PTE to well-defined teacher education fields, such as social justice, literacy, early childhood education, and communities of practice. Blending well- established theory with contemporary examples, this book is a great tool for teacher education faculty, doctoral students, and those interested in improving their PTE or supporting others in their PTE learning"--